Investigating Energy Performance Criteria in Compliance with Iranian National Building Regulations: The Role of Residential Building Envelope Adjacency - Payam Soltan Ahmadi; Ahmad Khoshgard; Hossein Ahmadi Danesh Ashtiani (Buildings)
Energy consumption modeling in buildings is crucial for calculating energy performance indices and establishing criteria for energy labeling. Different countries utilize diverse approaches to calculate these indices based on energy efficiency regulations and classifications. In recent years, Iran has established energy compliance standards, outlined in Article 19 of the National Building Regulations, to improve the energy efficiency of buildings. This study aims to develop a systematic methodology for assessing energy consumption indicators in residential buildings using the criteria specified in the Iranian National Building Regulations. Our research examines three specific energy standard categories in residential buildings to evaluate the suitability of the energy compliance specifications and identify the distribution of energy indices, rather than relying solely on the fixed values prescribed in the regulations. Initially, three model building shapes were analyzed to demonstrate how different building envelope designs affect energy performance. This study fills a critical research gap by estimating energy consumption indices through a novel methodology that combines regression analysis and Monte Carlo simulation for the three energy classifications specified in Article 19 of the Iranian National Building Regulations. The study employs a permutation approach to evaluate the primary energy consumption indicators and the uncertainties arising from various adjacency configurations. Extensive simulations were conducted, resulting in the development of regression equations that account for the surface area of the building envelope adjacent to the outdoor environment. The Monte Carlo method was used to assess potential fluctuations in the adiabatic area of the building envelope and the area adjacent to the external environment for buildings with varying orientations, allowing for the generation of probability distributions for energy consumption intensities. The sensitivity analysis identified the critical components of the building envelope and their orientation that significantly impact the uncertainty of energy efficiency. The findings revealed that the west and east walls of buildings adjacent to the outdoor environment substantially influence the uncertainty of energy consumption. In contrast, the floor surface and south wall had the least significant effect on annual energy uncertainty. This innovative approach represents a significant advancement in the field. It plays a specific role in energy labeling for buildings by calculating the required standard deviation in energy consumption indices resulting from various envelope adjacencies. This research also has practical implications for building design and energy efficiency measurement.